Dr. Manhattan’s Voice - Zittlaw, Jim (MacEwan University Student eJournal, 2014)
In this paper, the author analyzes the style of Dr. Manhattan’s narrating voice in the "Watchmaker" chapter of Alan Moore’s and Dave Gibbons’s Watchmen. The use of verbs, phrases, sentence structure, and formatting is examined and found to communicate effectively Dr. Manhattan’s unique worldview.